MUSICAL TRANSLITERATION OF TEPAK KENDANG ON FIGHTER GESTURES IN KENDANG PENCA - Dani Yanuar; Purwanto, Sigit (Acintya, 2024)
Kendang Penca is an art form that presents a complexity of interactions between the movements of fighters and the patterns of tepak kendang. The interaction between the two shows the connection between the language of movement and the language of music in building the concept of harmonious performance. From this interaction, the phenomenon of transliteration emerges, namely the process of translating the language of motion into the language of music, which in this case is the tepak kendang pattern. This research aims to reveal the process of transliterating the sound of tepak kendang music to martial arts movements in the Kendang Penca performance art. The problem posed is how the tepak kendang pattern and how the transliteration of the tepak kendang sound to the movements of the fighter is carried out. The theoretical concept of transliteration as part of the discipline of philology is used as a theoretical basis for examining research problems, while qualitative research methods with an ethnographic approach are used to guide researchers in extracting data, interpreting, and finding research conclusions. The results of this study reveal that the transliteration process carried out by the rider is framed by the concept of luyu aesthetics, so that the expression of the tepak kendang pattern presented is at the level of the perspective of appropriateness of the community supporting the art of kendang penca.